1994
DOI: 10.1051/radiopro/1994006
|View full text |Cite
|
Sign up to set email alerts
|

Thick oxide MOS transistors for ionizing radiation dose measurement

Abstract: The main properties of metal-oxide-silicon radiation dosemeters are described and the results obtained in terms of sensitivity and stability with thick oxide layers are given. Possible methods for improving their sensitivity are briefly discussed. RÉSUMÉLes principales propriétés des dosimètres de rayonnement métal-oxyde-semiconducteur (MOS) sont décrites. Nous présentons les résultats obtenus pour la sensibilité et la stabilité des dosimètres à oxyde de grille épais qui montrent que ce composant a des applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Many in ves ti ga tions [17][18][19][26][27][28][29][30][31][32][33] have shown that the ex po sure of MOS com po nents to gamma and X-ray ir ra di a tion leads to the in crease of elec tri cal charge in the in su lat ing gate ox ide (net pos i tive ox ide trapped charge) and in ter face charge (in ter face traps). The do sim e try of ion iz ing ra di a tion us ing MOS transis tor is based on the mea sure ment of pos i tive ox ide trapped charge in the gate ox ide Q ox and in ter face traps Q it .…”
Section: Discussionsmentioning
confidence: 99%
“…Many in ves ti ga tions [17][18][19][26][27][28][29][30][31][32][33] have shown that the ex po sure of MOS com po nents to gamma and X-ray ir ra di a tion leads to the in crease of elec tri cal charge in the in su lat ing gate ox ide (net pos i tive ox ide trapped charge) and in ter face charge (in ter face traps). The do sim e try of ion iz ing ra di a tion us ing MOS transis tor is based on the mea sure ment of pos i tive ox ide trapped charge in the gate ox ide Q ox and in ter face traps Q it .…”
Section: Discussionsmentioning
confidence: 99%
“…It was shown [33], [34] that sensitivity increases with gate voltage increase during irradiation and that it is higher in the case of positive gate bias, then negative gate bias (the lowest sensitivity is for zero gate bias). Furthermore, an increase in sensitivity can also be achieved with the increase in gate oxide layer thickness [35] and by processing conditions, which determine the FT density, their capture cross section and their location as well as the interface traps density [36].…”
Section: Radiation Sensitive Mosfet Parametersmentioning
confidence: 99%
“…It was shown that the response is linear for low doses and progressively saturates at a maximum values which respect to gate bias [40]. The linear dependence is given by [36] …”
Section: Important Pmos Dosimetric Parametersmentioning
confidence: 99%
“…In the case of positive gate bias, the sensitivity is higher, than in the case of negative gate bias and the lowest sensitivity being for zero gate bias [20]. Moreover, sensitivity increase can be achieved by increasing the gate oxide thickness [36][37][38][39] and by processing conditions which determine the FT density, their capture cross section and their location as well as the ST density [40].…”
Section: Important Pmos Dosimetric Parametersmentioning
confidence: 99%